Challenges to exotic disease preparedness in Great Britain: The frontline veterinarian's perspective. (24th June 2021) - Spence, Kelsey L.; Rosanowski, Sarah M.; Slater, Josh; Cardwell, Jacqueline M.
Abstract: Background: Exotic diseases pose a significant risk to horse health and welfare. Several stakeholder groups, including primary care veterinarians, share responsibility for maintaining freedom from pathogens that cause exotic diseases. However, little is known about the current state of exotic disease preparedness within the British horse industry. Objectives: The aim of this study was to explore equine veterinarians' experiences of, and attitudes towards, exotic disease preparedness in Great Britain. Study design: This is a qualitative interview‐based study. Methods: Semistructured interviews were conducted with 14 primary care equine veterinarians in Great Britain. Participants were purposively selected to include perspectives across varying levels of experience, clientele and location. All interviews were recorded, transcribed verbatim and analysed using thematic analysis. Results: Three themes were developed: (a) the reactive generalist, relating to participants' self‐concept of their role as primary care practitioners; (b) working within the bounds of influence, encompassing participants' perceived inability to influence their clients' knowledge and behaviours and (c) a fragmented horse industry, illustrating the wider culture in which participants worked, characterised by a lack of cohesion amongst its members. Main limitations: Only veterinarians' perspectives have been captured, so viewpoints from other stakeholders, such as horse owners and government officials, should be used to triangulate these findings. Conclusions: The findings suggest that improvements are required before an optimal level of exotic disease preparedness can be achieved. Additional support provided to frontline veterinarians, such as skills‐based training (ie, clinical reasoning and collaborative relationship building), accessible and trusted emergency support networks and clear expectations and responsibilities during an outbreak are recommended to optimise exotic disease preparedness.